Research about reading habits among children of ages between 0-12 in Extremadura - Soto Vázquez, José; Cordero Aparicio, Mª Esther; Jaraíz Cabanillas, Francisco Javier (Didáctica. Lengua y Literatura, 2019)
In this project, we have tried to bring together two essential ideas about reading in the rural field, with children of ages between 0-12 from a village in the Province of Extremadura called “Arroyo de la Luz”. In the first place, the database of the public library have been got mixing the information between the village’s people, the number of fellows and the books for borrowing from 2004 to 2016. The results obtained have been shown by means of graphics paying attention to the age and sex of the people. In the second place, a project of surveys has been carried out in Primary Schools so that the impartial data can be contrasted with the perception that young people have of their reading and cultural habits. The most relevant results confirm a higher reading index among girls of all ages; likewise, the genres most in demand are those of adventure and action; while we appreciate a gradual decline in reading habits in the age group analysed after six years.
Keywords: Reading habits; Elementary School; public library; surveys; Extremadura